A new species and new country records for the genus Leptobium Casey in the Palaearctic Region (Coleoptera: Staphylinidae: Paederinae) - Anlaş Si̇nan (Zootaxa, 2017)
Leptobium yagmuri Anlaş, sp. n., from central Anatolia, Turkey, is described, illustrated and distinguished from related congeners. New and additional country records of 19 Leptobium species in the Palaearctic Region are also reported; among them four species are first country records: Iraq (2), Italy (1) and Kazakhstan (1). A key to Turkish Leptobium is presented. Distributions of endemic Leptobium species in Anatolia are mapped.